Microvascular decompression for hemifacial spasm secondary to vertebrobasilar dolichoectasia: Surgical strategies, technical nuances and clinical outcomes. Issue 1 (January 2015) - Zaidi, Hasan A.; Awad, Al-Wala; Chowdhry, Shakeel A.; Fusco, David; Nakaji, Peter; Spetzler, Robert F.
Abstract Hemifacial spasm (HFS) due to direct compression of the facial nerve by a dolichoectatic vertebrobasilar artery is rare. Vessels are often non-compliant and tethered by critical brainstem perforators. We set out to determine surgical strategies and outcomes for this challenging disease. All patients undergoing surgery for HFS secondary to vertebrobasilar dolichoectasia were reviewed. Hospital records, clinic notes and radiographic imaging were collected for outcome measures. Seventeen patients (eight males, nine females) were identified. Sixteen patients (94%) were treated with Teflon pledgets (DuPont, Wilmington, DE, USA) and one (6%) patient had a vascular sling placed around a severely diseased vertebral artery. All patients had significant reduction in symptoms and 82% of patients had complete resolution of symptoms (average follow-up: 41.4 months). One patient suffered persistent facial nerve paresis and swallowing difficulty. Two other patients suffered a 1 point decrease in the House–Brackmann facial nerve grading scale. Four patients (23%) required re-operation (infection, cerebrospinal fluid leak, and two patients with delayed recurrence of HFS). Of the latter, one patient required repositioning of a Teflon pledget and another patient underwent a sling decompression. There were no perioperative strokes or death. Excellent relief of symptoms with acceptable preoperative morbidity can be achieved using Teflon pledgets alone in most cases. In recalcitrant cases, sling transposition can be used to further augment the decompression. Careful attention must be paid to prevent vascular kinking and preserve brainstem perforators.